The violence of incarceration - Scraton, Phil (Routledge advances in criminology, 2008)
The violence of incarceration : an introduction / Jude McCulloch and Phil Scraton -- An afternoon in September 1983 / Laurence McKeown -- Entombing resistance : institutional power and polarisation in the Jika Jika High-Security Unit / Bree Carlton -- Protests and "riots" in the violent institution / Phil Scraton -- Child incarceration : institutional abuse, the violent state, and the politics of impunity / Barry Goldson -- Naked power : strip-searching in women's prisons / Jude McCulloch and Amanda George -- The imprisonment of women and girls in the north of Ireland : a "continuum of violence" / Linda Moore and Phil Scraton -- Neither kind nor gentle : the perils of "gender responsive justice" / Cassandra Shaylor -- The US military prison : the normalcy of exceptional brutality / Avery F. Gordon -- A reign of penal terror : US global statecraft and the technology of punishment and capture / Dylan Rodríguez -- Indigenous incarceration : the violence of colonial law and justice / Chris Cunneen -- The violence of refugee incarceration / Jude McCulloch and Sharon Pickering -- Preventing torture and casual cruelty in prisons through independent monitoring / Diana Medlicott